Shiver - Reynolds, Allie (2020)
"In this propulsive locked-room thriller debut, a reunion weekend in the French Alps turns deadly when five friends discover that someone has deliberately stranded them at their remote mountaintop resort during a snowstorm. When Milla accepts an off-season invitation to Le Rocher, a cozy ski resort in the French Alps, she's expecting an intimate weekend of catching up with four old friends. Yet no sooner do Milla and the others arrive for the reunion than they realize something is horribly wrong. Stranded in the deserted resort, Milla's not sure what's worse: the increasingly sinister things happening around her or the looming snowstorm that's making escape even more impossible. All she knows is that there's no one on the mountain she can trust." --
Keywords: Winter storms -- Fiction; Ski resorts -- Fiction; Friendship -- Fiction; Murder -- Fiction; Reunions -- Fiction; Snowboarders -- Fiction; Secrecy -- Fiction; Alps, French (France) -- Fiction; Suspense fiction; Thrillers (Fiction); Detective and mystery fiction